2021
DOI: 10.5902/2316546465434
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre sintomas depressivos e nível de atividade física de adolescentes do ensino médio técnico do IFCE campus Canindé

Abstract: O presente estudo tem como objetivo verificar a relação entre sintomas depressivos e nível de atividade física de adolescentes do ensino médio técnico do IFCE campus Canindé. Trata-se de um estudo de campo, descritivo, do tipo transversal e de abordagem quantitativa. Para avaliar os sintomas depressivos foi utilizado o questionário Inventário de Depressão Infantil (CDI) e para verificar o nível de atividade física foi utilizado o Questionário de Atividade Física (QAFA). Os resultados do estudo mostraram que 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
0
0
Order By: Relevance
“…It was observed, in the present study, that the higher the risk of symptoms of depression, the lower the chance of association with the practice of physical activity, which corroborates the results of the study conducted with young people regularly enrolled in the country's public school system, which found that there is a tendency for adolescents with low levels of physical activity to present depressive symptoms and higher levels of stress 28 . In this regard, the need for actions that favor the early identification of adolescents with symptoms of depression in order to act strategically with this public is highlighted.…”
Section: Discussionsupporting
confidence: 91%
“…It was observed, in the present study, that the higher the risk of symptoms of depression, the lower the chance of association with the practice of physical activity, which corroborates the results of the study conducted with young people regularly enrolled in the country's public school system, which found that there is a tendency for adolescents with low levels of physical activity to present depressive symptoms and higher levels of stress 28 . In this regard, the need for actions that favor the early identification of adolescents with symptoms of depression in order to act strategically with this public is highlighted.…”
Section: Discussionsupporting
confidence: 91%
“…Observou-se, no presente estudo, que quanto maior o risco de sintomas de depressão menor é a chance de associação com a prática de atividade física, o que corrobora os resultados do estudo realizado com jovens regularmente matriculados na rede pública de ensino do país, o qual verificou que há uma tendência de adolescentes com níveis baixos de atividade física apresentarem sintomas depressivos e níveis de estresse mais elevados 28 . Atinente a isso, destaca-se a necessidade de ações que favoreçam a identificação precoce dos adolescentes com sintomas de depressão a fim de atuar estrategicamente junto a esse público.…”
Section: Discussionunclassified